Anaemia among women of reproductive age in selected sub-Saharan African countries: multivariate decomposition analyses of the demographic and health surveys data 2008–2018 - Salifu, Mohammed Gazali; Da-Costa Vroom, Frances Baaba; Guure, Chris (Frontiers in Public Health, 2024)
The burden and highest regional prevalence of anaemia is reported in sub-Saharan Africa (SSA). The study evaluated changes in anaemia prevalence across DHS survey periods in SSA and reported factors influencing observed trend changes and.The study was implemented via a two-stage cross sectional stratified sampling approach. Women of reproductive age (15 -49 years) in four (Ghana, Sierra Leone, Mali, and Benin) sub-Saharan Africa countries using two different periods of their Demographic Health Surveys (DHS) data were used. The study adopted both descriptive and inferential statistical methods. Chi-square test was used to determine the existence of statistically significant relationship between the outcome and predictor variables and to test observed changes in anaemia. Multivariable logistic regression analyses were carried out on each survey year and the pooled dataset for eligible study countries. country. Multivariate decomposition analysis was performed to explain how compositional changes and behavioural effects of women characteristics affected the changes in anaemia prevalence. Frequencies, percentages were reported as well as odds ratios at 95% confidence interval (CI).Results: Ghana and Sierra Leone experienced 17.07% [95% CI: 14.76-19.37, p<0.001] and 1% [95% CI: 1.0 -2.9, p>0.05] anaemia decrease from period 1 to period 2 respectfully whilst Mali and Benin experienced 11% [95% CI: 9.14-12.90 p<0.001] and 16.7% [95% CI: 14.99-18.5 p<0.001] increase in anaemia prevalence from period 1 to period 2. Behavioural effects explained the decrease in Ghana and explained the increases in Benin and Mali while endowments or compositional changes explained the decrease in Sierra Leone.Anaemia continues to be extremely high in sub-Saharan Africa. Therefore, there is the urgent need to scale up implementation of nutrition-related programs and advocacies to ensure optimum changes in women nutrition related behaviours.